Environmental cues for healthy food marketing: The importance of in-store research into three conversions - Larsen, Nils Magne; Sigurdsson, Valdimar; Gunnarsson, Didrik (Frontiers in Nutrition, 2022)
Since retailers control the space where consumers tend to make the vast majority of their food purchase decisions, they can take measures to promote healthy living. Increasing relative sales of healthy food can contribute to the ongoing battle against preventable lifestyle diseases. We show how retailers can use impression management and environmental cues in their stores to influence consumers’ sales responses to healthy food. This paper advocates in-store research in this realm and introduces three consumer behavior levels - reaching, stopping/holding, and closing the sale - as micro-conversions when retailers use impression management on their consumers. We showcase impression management at each conversion level by testing the effects of placing healthy and unhealthy food items on a floor display in the store area with the most traffic, with or without background music and an advertisement. The results demonstrate that a healthy food product can outperform the sales of popular unhealthy foods. The floor display, for example, increased the sales of the targeted “healthy product” by 570% on average during the intervention periods, compared with the baseline. We discuss the importance of in-store research into three conversions to enable further development of impression management and the use of environmental cues for healthy food promotion.